2018
DOI: 10.1007/s12020-018-1687-0
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric pituitary adenomas in Northeast Mexico. A follow-up study

Abstract: PurposeTo review incidence, treatment and outcome of pediatric pituitary adenomas (PAs).MethodsA follow-up study patients with the age of ≤19 years old who were treated from 1995 to 2015 in Mexico.ResultsOut of 1244 diagnosed PA, 43 patients were children (35 females, 8 males) with a mean age of 17.2 years. The majority were macroadenomas (70%) with prolactinomas (PRL) dominating (63%) followed by non-functioning adenomas (21%). In total, 40% were diagnosed as invasive. Growth hormone (GH) secreting adenomas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…It has been reported that pituitary adenomas are more common in females, and female predominance has been reported to be as high as 3.3:1 in the young population [24]. In our cohort, there was a female predominance of 1.9:1, which is consistent with the literature.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It has been reported that pituitary adenomas are more common in females, and female predominance has been reported to be as high as 3.3:1 in the young population [24]. In our cohort, there was a female predominance of 1.9:1, which is consistent with the literature.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that the most common pituitary adenomas in children are prolactinomas and corticotropinomas, and NFAs are extremely rare [3,15,16,24]. The articles reporting the highest percentages of NFA in the systematic review were Zhan et al [12] (26.8%), Giovinazzo et al…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[4] Pituitary adenomas (PA) are classified according to the 4th edition of the World Health Organization (WHO) 2017 guidelines by their immunohistochemical labelling, according to the somatotropic (GH), lactotropic (PRL), gonadotropic (FSH/LH), corticotropic (ACTH) or thyrotropic (TSH) contingent. [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity between groups: p = 0.022 Overall (I 2 = 71.34%, p = 0.00); Cannavò et al [36] Andereggen et al [30] Di Sarno et al [31] Tamasauskas et al [17] Babey et al [16] Vale et al [33] Barber et al [35] Andereggen et al [30] Micko et al [39] Medication Wolfsberger et al [41] Subtotal (I 2 = 74.35%, p = 0.00) Subtotal (I 2 = 7.88%, p = 0.37) Sala et al [34] Torres-García et al [38] Study Yi et al [18] Martin de Santa-Olalla y Llanes et al [32] Kreutzer et al [40] Andereggen et al [ Babey et al [16] Subtotal (I 2 = 77.49%, p = 0.00) Figure 4: Meta-analysis of remission rates comparing surgery and medical treatment in microprolactinomas after treatment withdrawal and the results of subgroup analysis: (a) the remission rate was achieved in 78% of patients treated with surgery and 44% of patients treated with DAs (P � 0.003) after treatment withdrawal and (b) the remission rate was achieved in 92% of patients with preoperative PRL level of ≤200 ng/ml and 40% of patients with preoperative PRL level of >200 ng/ml (P � 0.029).…”
Section: Discussionmentioning
confidence: 99%